2019
DOI: 10.1021/acs.orglett.9b04575
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structures, and Properties of Neutral and Radical Cationic S,C,C-Bridged Triphenylamines

Abstract: A structurally constrained S,C,C-bridged triphenylamine was synthesized, and the corresponding radical cation was obtained as a hexachloroantimonate by chemical oxidation. An X-ray crystallographic analysis revealed an almost planar structure for this radical cation, which thus represents the first example of a planar, para-unsubstituted triphenylamine radical cation analogue with a sulfur bridge. The electronic properties of the radical cation were examined by UV–vis–NIR and ESR spectroscopy as well as DFT ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 28 publications
2
23
0
Order By: Relevance
“…Recently, there has been much progress in designing new amine radical cations based upon this triarylamine. [85][86][87] Persulfate salts. The anion of Marshall's acid (peroxydisulfuric acid, H 2 S 2 O 8 ) is a strong oxidising agent (E red = +1.76 V vs. SCE).…”
Section: Scheme 12mentioning
confidence: 99%
“…Recently, there has been much progress in designing new amine radical cations based upon this triarylamine. [85][86][87] Persulfate salts. The anion of Marshall's acid (peroxydisulfuric acid, H 2 S 2 O 8 ) is a strong oxidising agent (E red = +1.76 V vs. SCE).…”
Section: Scheme 12mentioning
confidence: 99%
“…In 2020, Kato et al reported the preparation of the sulfur-containing azatriangulene analogues 114.4 – 5 ( Scheme 114 ). 227 The intermediate 114.2 was obtainable from the Ullmann-type reaction between dimethyl 2-iodoisophthalate ( 114.1 ) and phenothiazine. Compound 114.2 was then treated with MeMgBr to give the diol 114.3 .…”
Section: Pyrenoidsmentioning
confidence: 99%
“…At the heart of the issue was the fact that there are really two styles (at least) of using bold lines in the organic literature. 15 One uses solid bold lines for the bonds closest to the viewer, and the other augments these with lines that taper from bold close to the viewer to thin farther away in an effort to provide an additional sense of perspective and three-dimensionality. After a rather heated discussion about which type of representation would better convey the chemical information that we wanted to convey, we reached an impasse and decided to agree that both had merits in this regard.…”
Section: Choosing the “Worst” Picture For Publicationmentioning
confidence: 99%